Folk etymology and contamination in the Romance languages - Maiden, M (Oxford University Press, 2020)
‘Folk etymology’ and ‘contamination’ each involve associative formal influences between words which have no ‘etymological’ (i.e., historical), connexion. From a morphological perspective, in folk etymology a word acquires at least some elements of the structure of some other, historically unrelated, word. The result often looks like a compound, of a word composed of other, independently existing, words. These are usually (but not necessarily) ‘compounds’ lacking in any semantic compositionality, which do not ‘make sense’: for example, French beaupré ‘bowsprit’, but apparently ‘beautiful meadow’, possibly derived from English bowsprit. Typically involved are relatively long, polysyllabic, words, characteristically belonging to erudite or exotic vocabulary, whose unfamiliarity is accommodated by speakers unfamiliar with the target word through replacement of portions of that word with more familiar words. Contamination differs from folk etymology both on the formal and on the semantic side, usually involving non-morphemic elements, and acting between words that are semantically linked: for example, Spanish nuera ‘daughter-in-law’, instead of etymologically expected **nora, apparently influenced by the vowel historically underlying suegra ‘mother-in-law’. While there is nothing uniquely Romance about these phenomena, Romance languages abound in them.